In silico analysis for discovery of dengue virus inhibitor from natural compounds - Roney, Miah; Hossain, Md. Sanower; Mohd Fadhlizil Fasihi, Mohd Aluwi (Atlantis Press, 2022)
Dengue fever is a growing global health problem, with millions of virus illnesses occurring each year. Unfortunately, there is no approved treatment available. DENV NS5 RdRp protease produced by the dengue virus (DENV) is being investigated as a promising therapeutic target for developing efficient dengue treatments. Dengue virus propagation is aided by RdRp protease. This work used in-silico ligand-based and structure-based techniques to generate a DENV-2 NS5 RdRp protease inhibitor. Firstly, a ligand-based Lipinski's rule of five and an ADMET prediction was utilized to screen 42 putative antiviral natural compounds. The tested compounds were docked into the active region of DENV-2 NS5 RdRp protease. A lead compound (3'-O-Methyldiplacol) is recommended as a promising inhibitor of NS5 RdRp protease based on docking scores. This work discovered a possible DENV-2 NS5 RdRp protease inhibitor applying in-silico screening that might be beneficial in treating Dengue. Studying the effectiveness of this compound through in vitro and in vivo experimentations must be warranted.